Efectos de las exenciones y exoneraciones en la recaudación del impuesto a la renta del sector camaronero. - Jimenez Apolo, Maria Esther (My University, 2018)
The collection of taxes represents a significant fiscal tool for the state, thanks to which the government will not only be able to pay for public expenditures, but also fulfill its main obligation to manage public resources and channel them towards investment in infrastructure and services that will boost the economic and social development of the country, besides guaranteeing economic stability by fostering employment sources and generating foreign exchange. In the province of El Oro, shrimp farming is a fundamental pillar in the economic stability due to the considerable amount of hectares destined to this sector that provide sources of employment for the people of Ore. This sector generates more than $ 2,500 million dollars per year, therefore, a significant amount for the collection of taxes for this profitability. Although this sector can generate significant revenues for the State budget in terms of tax collection, the excess of tax burdens to this sector will discourage this activity, and alienate private investment; This can cause a decrease in sources of work affecting the economic and social field. That is why, in order to encourage investment and the undertakings of shrimp companies, the authorities in charge analyze and establish exemptions or exemptions that are defined as tax benefits or incentives whose purpose is to promote the development and promotion of this sector. For this reason, this work focuses on analyzing the effects of exemptions and exemptions from income tax and demonstrate how it impacts the shrimp sector.
La recaudación de tributos representa una significativa herramienta fiscal para el estado, gracias a ella el gobierno podrá no solamente solventar los gastos públicos, sino también cumplir con su principal obligación de gestionar los recursos públicos y canalizarlos hacia la inversión en infraestructura y servicios que impulse el desarrollo económico y social del país, además de garantizar estabilidad económica fomentando fuentes de empleo y generación de divisas. En la provincia de El Oro la actividad camaronera es un pilar fundamental en la estabilidad económica debido a la cantidad considerable de hectáreas destinadas a este sector que proporcionan fuentes de empleo para los orenses. Este sector genera más de $2.500 millones de dólares al año, por tanto, una cantidad significativa para el cobro de tributos por esa rentabilidad. Si bien este sector puede generar ingresos significativos para el presupuesto del Estado en materia de recaudación de impuestos, el exceso de cargas tributarias a este sector desalentara esta actividad, y alejara la inversión privada; esto puede provocar disminución de fuentes de trabajo afectando el campo económico y social. Es por eso que, con el propósito de incentivar la inversión y los emprendimientos de sociedades camaroneras, las autoridades encargadas analizan y establecen exoneraciones o exenciones que se definen como beneficios o estímulos tributarios cuya finalidad es fomentar el desarrollo e impulso de este sector. Por tal motivo, este trabajo se enfoca en analizar los efectos de las exoneraciones y exenciones del impuesto a la renta y demostrar cómo impacta en el sector camaronero.
Keywords: IMPUESTOS; RECAUDACIÓN TRIBUTARIA; BENEFICIOS FISCALES; EXENCIONES; ADMINISTRACIÓN PÚBLICA